Burnout in Elite Athletes: Psychological Causes and Prevention Strategies (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Burnout in elite athletes is a multidimensional psychological syndrome characterized by emotional and physical exhaustion, reduced sense of accomplishment, and sport devaluation. Increasing performance expectations, intense training loads, competitive pressure, and psychosocial stressors have intensified the prevalence of burnout in high-performance sports. Recent psychological research highlights the central role of stress, maladaptive coping strategies, low resilience, motivational climate, and lack of social support as key contributors to burnout development. Empirical evidence suggests that life stress, emotional dysregulation, perfectionism, and chronic workload imbalance significantly elevate burnout risk. Conversely, resilience, problem-focused coping, mindfulness, emotional regulation, and psychosocial resources act as protective factors. Prevention strategies emphasize psychological skills training, stress management interventions, resilience development, supportive coaching environments, and systematic workload monitoring. This study synthesizes current theoretical and empirical perspectives on the psychological causes and prevention strategies of burnout in elite athletes. The analysis highlights the necessity of adopting a holistic, athlete-centered approach that integrates mental health support with training management to enhance well-being, performance sustainability, and career longevity. Understanding burnout through psychological frameworks can facilitate the design of evidence-based interventions, promoting healthier and more adaptive sporting environments.